Peculiar Attunements : How Affect Theory Turned Musical - Grant, Roger Mathew (Book collections on Project MUSE., 2020)
"Peculiar Attunements places the recent turn to affect into conversation with an earlier affective turn that took place in European music theory of the eighteenth century. It offers a new way of thinking through affect historically and dialectically, drawing attention to repeating patterns and problems in affect theory's history"--